1996
DOI: 10.1042/bj3180603
|View full text |Cite
|
Sign up to set email alerts
|

Changes associated with aging and replicative senescence in the regulation of transcription factor nuclear factor-κB

Abstract: Both the aging of animals and the senescence of cultured cells involve an altered pattern of gene expression, suggesting changes in transcription factor regulation. We studied age-related changes in transcription factors nuclear factor (NF)-kappa B, activator protein factor-1 (AP-1) and Sp-1 by using electrophoretic mobility shift binding assays; we also analysed changes in the protein components of NF-kappa B complex with Western blot assays. Nuclear and cytoplasmic extracts were prepared from heart, liver, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(154 citation statements)
references
References 30 publications
12
137
0
5
Order By: Relevance
“…These observations suggest that NF-κB activation not only negatively, but also positively regulates apoptosis. This idea has been further strengthened by studies on NMRI mice, Wistar rats, and WI-38 fibroblasts where aging induced a strong and consistent increase in the nuclear binding activity of NF-κB (Helenius et al, 1996).…”
Section: Pro-apoptotic Activity Of Nf-κbmentioning
confidence: 96%
“…These observations suggest that NF-κB activation not only negatively, but also positively regulates apoptosis. This idea has been further strengthened by studies on NMRI mice, Wistar rats, and WI-38 fibroblasts where aging induced a strong and consistent increase in the nuclear binding activity of NF-κB (Helenius et al, 1996).…”
Section: Pro-apoptotic Activity Of Nf-κbmentioning
confidence: 96%
“…Recent reports demonstrated the NF-jB-dependent induction of miR-146a expression by TLR signaling (Taganov et al, 2006;Cameron et al, 2008;Lukiw et al, 2008). Although details about the mechanisms of immunosenescence have yet to be elucidated, many studies have been conducted in aged humans to establish a clear correlation between an increase in the constitutive activation of NF-jB and chronic inflammation (Helenius et al, 1996;Spencer et al, 1997;Kim et al, 2002;Sarkar & Fisher, 2006). Our studies demonstrated that an appreciable rise in miR-146a expression was correlated with an age-dependent augmentation of the binding of NF-jB p65 to the miR-146a promoter in macrophages from aged mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…of three independent experiments. Note that the relative activities of the di erent constructs should not be compared, as each one of them was assayed with di erent protein amounts in order to optimally assess their respective growth factor responsiveness exhibit lower NF-kB-mediated transcriptional activity (Helenius et al, 1996). Similarly, lowered induction of NF-kB in human activated T lymphocytes was noted during aging (Trebilcock and Ponnappan, 1996).…”
Section: Of Three Independent Experimentsmentioning
confidence: 99%